Identifikasi Penyakit Aeromonad pada Budi Daya Ikan Air Tawar di Bali (IDENTIFICATION OF AEROMONAD DISEASE IN FRESH WATER AQUACULTURE IN DENPASAR, BALI) - Amanu, Surya; ., Kurniasih; Indaryulianto, Soedarmanto (Jurnal Veteriner, 2015)
Fresh water and marine fish horticulture in Bali is often harmed by the outbreak of diseases such asthose caused by Aeromonas sp (aeromonad disease).Aims ofstudy were 1) to find out the primary agent ofthe aeomonad disease in the fresh water aquaculture in Bali based on conventional and molecularidentification, 2) to find out the genetic variability of Aeromonas species, 3) to determine the effectiveantibiotic against the agent. Samples of fishes were collected from 5 different locations of fresh wateraquaculture that had high number of morbidity and mortality. Many different fishes which showed clinicalsign such as skin lesion and exophthalmus were collected.Aeromonas hydrophila and A. salmonicida wereisolated and identified from fishes, they were then identified molecularly with DNA extraction, DNAamplification in 16S rRNA gene, purification and sequencing. Sequences of both Aeromonas species fromdifferent location were analysed to create the phylogenetic tree with Maximum Parsimony and NeighborJoining method. Sensitivity of 5 antibiotics to both species of Aeromonas were done to determine the bestantibiotic against the disease. Aeromonad disease were found only in 3 regions in Bali. As many as 10isolates of A.salmonicida and 11 isolates of A.hydrophila were examined. The histopathological examinationshowed dermatitis, epicarditis, retinitis, liver and kidney congestion in fish.There were two clusters ofA.salmonicida, subspecies smithiaand subspecies achromogenes.Aeromomas hydrophyla had a close relationwith A. veronii.Aeromonas salmonicida subspecies salmonicida has not been found in Bali. Enrofloxacineand gentamycin was the best antibiotic for treating the Aeromonad disease which were more effective ascompared to3 other antibiot ics (Ampicillin, Doxycycline, and Eritromycin).
Keywords: Aeromonas hydrophyla, A. salmonicida, phylogenetic tree, histopathology